(3GdahGFO GdefJbGI GdYhGdi Yf GdTjhN GdKbGJs - (3CHh SYO GdeXaQ Hf GdMSf Hf GdSHWs ((3CMeO Hf YHO Gdedc GdebOS s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdKbI CHh GdbGSe gHI Gddg Hf GdMSf GdSHW abGd (B: (3bGe ajfG QShd Gddg Udi Gddg Ydjg hSde , abGd (B: (3CcQehG CUMGHi Ke GdPjf jdhfge GdMOjK s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde Ef GdESdGe HOC ZQjHkG hSjYhO ceG HOC aWhHi ddZQHGA bjd (B: (3heG GdZQHGA ? bGd (B: (3GdfRGY ef GdbHGFd BNQ GdLRA s
(3HgG fXGe GdJYbjHIs
(3QhGjI hdOg CHj Ydi GdMSf Hf GdeXaQ Hf GdMSf HBNQgG SeGYGJ fajSI LOkG Ydi cHGQ GdYdeGA ai GdbQf GdSGOS hGdSGOS hGdSGHY hGdKGefs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3eLGejY (B124) s
Keywords: (3GdMOjK h GdeUWdMs